Does sleep disruption mediate the effects of childhood maltreatment on brain structure?. (15th December 2017) - Teicher, Martin H.; Ohashi, Kyoko; Khan, Alaptagin; Hernandez Garcia, Laura C.; Klengel, Torsten; Anderson, Carl M.; Silveri, Marisa M.
ABSTRACT: Background : Childhood maltreatment is associated with alterations in morphology of stress susceptible brain regions. Maltreatment is also known to markedly increase risk for psychopathology and to have an enduring disruptive effect on sleep. Objective : To determine whether abnormalities in sleep continuity have effects on brain morphometry and to evaluate the extent to which sleep impairments mediate the effects of maltreatment on brain structure. Method : Maltreatment and Abuse Chronology of Exposure (MACE) scale ratings, actigraph-assessed sleep and 3T MRI were obtained on N  = 37 18–19-year-old participants recruited from the community ( N  = 34 with neuroimaging). Results : Fourteen participants had no history of maltreatment while N  = 23 were exposed, on average, to 4.7 types of maltreatment. Multiplicity of maltreatment was strongly associated with reduced sleep efficiency, increased wake after sleep onset time and number/duration of awakenings, which were independent of effects of maltreatment on depression and anxiety. The most important predictors of impaired sleep were exposure to parental non-verbal emotional abuse at 9–10 years of age. Reduced sleep efficiency correlated with reduced grey matter volume in hippocampus including CA1 subfield, molecular layer and dentate gyrus as well as inferior frontal gyrus and insula. Sleep mediated 39–46% of the effects of maltreatment on volume of hippocampal structures and inferior frontal gyrus. Conclusions : Actigraph-assessed sleep is disrupted in maltreated late teens and mediates a significant portion of the effects of maltreatment on hippocampal volume. Studies are needed to assess whether efforts to enhance sleep in maltreated children can pre-empt or ameliorate neurobiological consequences of maltreatment.